2007
DOI: 10.1007/s12070-007-0088-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bismuth subgallate and adrenaline paste as haemostat in tonsillectomy bleeding

Abstract: Haemorrhage is a frequent and often feared complication of tonsillectomy. This has prompted the use of a variety of topical haemostatics such as bismuth subgallate to achieve haemostasis and reduce the risk of postoperative haemorrhage. In this study effect of bismuth subgallate and adrenaline paste was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In accordance with other studies, we observed an improvement in the time required for the achievement of hemostasis with the use of adrenaline (Rasgon et al, 1991;Sharma et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with other studies, we observed an improvement in the time required for the achievement of hemostasis with the use of adrenaline (Rasgon et al, 1991;Sharma et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…This has prompted the use of a variety of topical haemostatic agents such as bismuth subgallate and adrenaline to achieve hemostasis and reduce the risk of intra and postoperative hemorrhage (Rasgon et al, 1991;Agrawal et al, 2005;Sharma et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Hatton et al reported that topical adrenaline is an effective hemostatic agent in tonsillectomy 11 . The application of bismuth subgallate and adrenaline paste to the tonsillar fossae reduced the operating time by 23% and blood loss by 21% 27 . Epinephrine, a platelet-stimulating agent, can cause aggregation of human platelets through alpha-adrenergic mechanisms 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Hatton et al reported that topical adrenaline is an effective hemostatic agent in tonsillectomy [ 11 ]. The application of bismuth subgallate and adrenaline paste to the tonsillar fossae reduced the operating time by 23% and blood loss by 21% [ 28 ]. Epinephrine, a platelet-stimulating agent, can cause aggregation of human platelets through alpha-adrenergic mechanisms [ 29 ].…”
Section: Discussionmentioning
confidence: 99%